Let -pi/6<theta<-pi/12. Suppose a1 and b1 are the roots of the equation x2 - 2xsec(theta) + 1=0 and a2 and b2 are the roots of the equation x2 + 2xtan(theta) - 1=0. If a1>b1 and a2>b2, then a1 + b2 is???

Dear Student,
Please find below the solution to the asked query:

x2-2xsecθ+1=0Using Shridharacharya's formula we get:x=--2secθ±-2secθ2-4×1×12×1=2secθ±4sec2θ-42=2secθ±2sec2θ-12=secθ±tan2θ=secθ±tanθAs -π6<θ<-π12, hence tanθ will be negative.tanθ=-tanθx=secθtanθa1=secθ-tanθa2=secθ+tanθx2+2xtanθ-1=0x=-2tanθ±-2tanθ2-4×1×1-12×1=-2tanθ±4tan2θ+42=-2tanθ±2tan2θ+12=-2tanθ±2sec2θ2=-tanθ±secθAs secθ is positive when -π6<θ<-π12secθ=secθx=-tanθ±secθ, hence roots arex=secθ-tanθ and x=-secθ-tanθAs a1=secθ-tanθa2=secθ+tanθNote that secθ-tanθ is positiveand a1>b1 and a2>b2b1=-secθ-tanθandb2=secθ-tanθBut in that caseb2>a2assecθ-tanθ>-secθ-tanθNo combination fits a1>b1 and a2>b2You can also see that in the graph given below.


Hope this information will clear your doubts about this topic.

If you have any doubts just ask here on the ask and answer forum and our experts will try to help you out as soon as possible.
Regards

  • -20
What are you looking for?